Cancers Attributable to Alcohol Consumption in Nigeria: 2012–2014 - Odutola, Michael Kolawole; Jedy-Agba, Elima E.; Dareng, Eileen O.; Adebamowo, Sally N.; Oga, Emmanuel A.; Igbinoba, Festus; Otu, Theresa; Ezeome, Emmanuel; Hassan, Ramatu; Adebamowo, Clement A. (Frontiers in Oncology, 2017)
Introduction Alcohol consumption has been identified as a risk factor for many cancers but less attention has been paid to the fraction of those cancers that are attributable to alcohol consumption. In this study, we evaluated the incidence and population attributable fraction (PAF) of cancers associated with alcohol consumption in Nigeria. Methods We obtained data on incidence of cancers from two Population Based Cancer Registries (PBCRs) in Nigeria and identified cancer sites for which there is strong evidence of an association with alcohol consumption based on the IARC Monograph 100E. We computed the population attributable fraction (PAF) for each cancer site by age and sex, using prevalence and relative risk estimates from previous studies. Results Between 2012 to 2014 study period, the PBCRs reported 4,336 cancer cases of which 1,627 occurred in males, and 2,709 occurred in females. Of these, a total of 1,808 cancer cases, 339 in males and 1,469 in females, were associated with alcohol intake. The ASR of alcohol associated cancers was 77.3 per 100,000. Only 4.3% (186/4,336) of all cancer cases or 10.3% (186/1,808) of alcohol associated cancers were attributable to alcohol consumption. Some 42.5% (79/186) of these cancers occurred in males while 57.5% (107/186) occurred in females. The ASR of cancers attributable to alcohol in this population was 7.2 per 100,000. The commonest cancers attributable to alcohol consumption were cancers of the oral cavity and pharynx in men and cancer of the breast in women. Conclusion Our study shows that 4.3% of incident cancers in Nigeria can be prevented by avoiding alcohol consumption. While the incidence of cancers associated with alcohol intake is high, the proportion attributable to alcohol consumption is much lower suggesting that the number of cancers that may be prevented by eliminating alcohol intake in this population is relatively low.